2010
DOI: 10.1007/s11104-010-0490-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate nutrition enhances zinc hyperaccumulation in Noccaea caerulescens (Prayon)

Abstract: Nitrate fertilization has been shown to increase Zn hyperaccumulation by Noccaea caerulescens (Prayon) (formerly Thlaspi caerulescens). However, it is unknown whether this increased hyperaccumulation is a direct result of NO 3 − nutrition or due to changes in rhizosphere pH as a result of NO 3 − uptake. This paper investigated the mechanism of NO 3 − -enhanced Zn hyperaccumulation in N.caerulescens by assessing the response of Zn uptake to N form and solution pH. Plants were grown in nutrient solution with 300… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 64 publications
5
33
0
Order By: Relevance
“…As a result, Cd hyperaccumulation in S. plumbizincicola was largely enhanced by NO 3 -supplementation rather than NH 4 + ( Table 2). This is consistent with previous studies showing that NO 3 -fertilisation led to both higher biomass production and higher Cd and Zn extraction than NH 4 + in N. caerulescens (Schwartz et al 2003;Monsant et al 2008Monsant et al , 2010Monsant et al , 2011Xie et al 2009), camomile (Kovacik et al 2011) and tomato . The stimulated uptake of nutrient elements such as Ca and K may be partly responsible for the stimulation of plant growth.…”
Section: Plant Biomass and CD Accumulationsupporting
confidence: 93%
See 1 more Smart Citation
“…As a result, Cd hyperaccumulation in S. plumbizincicola was largely enhanced by NO 3 -supplementation rather than NH 4 + ( Table 2). This is consistent with previous studies showing that NO 3 -fertilisation led to both higher biomass production and higher Cd and Zn extraction than NH 4 + in N. caerulescens (Schwartz et al 2003;Monsant et al 2008Monsant et al , 2010Monsant et al , 2011Xie et al 2009), camomile (Kovacik et al 2011) and tomato . The stimulated uptake of nutrient elements such as Ca and K may be partly responsible for the stimulation of plant growth.…”
Section: Plant Biomass and CD Accumulationsupporting
confidence: 93%
“…However, the differences in water uptake cannot fully explain the differences in local velocity of Cd transport (3.7-fold) and the differences in Cd distribution between these two N treatments. Comparatively, it is suggested that unlike NH 4 + which is mainly assimilated or stored in the roots, NO 3 -is translocated as a hydrated anion in the xylem where cationic charges are required for charge balance (Monsant et al 2010 (Arnozis and Findenegg 1986;Turan and Sevimli 2005). This is consistent with our results showing that concentrations of the cations Ca and K in the xylem sap increased but the anion P was inhibited in the NO 3 -treatment compared with the NH 4 + treatment (Table 1).…”
Section: Translocation From Root To Shootsupporting
confidence: 91%
“…of the Zn is in the upper and lower epidermis whereas only 12.4% of Zn remains in the mesophyll cells (Monsant et al, 2010). In contrast to the overall plant distribution of Zn among tissue and cell types, Zn accumulation in the epidermis occurs mainly in the vacuoles, and to a lesser extent in the apoplast.…”
Section: A C C E P T E D Mmentioning
confidence: 92%
“…High concentrations of Zn in vacuoles and cell walls (apoplast) of epidermal cells are observed to always associate with high concentrations of Ca (Vazquez et al, 1994), and in leaf cells of N. caerulescens it is found that Zn and Ca can co-locate (Monsant et al, 2010). The Zn and Ca concentrations are 36000 and 8600 mg kg -1 , respectively, in the upper epidermis in the leaf and 20000 and 6200 mg kg -1 , respectively, in the lower epidermis.…”
Section: A C C E P T E D Mmentioning
confidence: 93%
See 1 more Smart Citation